A Preliminary Study on the Effect of Psyllium Husk Ethanolic Extract on Hyperlipidemia, Hyperglycemia, and Oxidative Stress Induced by Triton X-100 Injection in Rats - Mohamed A. Hashem; Noura A. Abd-Allah; Essam A. Mahmoud; Shimaa A. Amer; Mohamed Alkafafy (Biology, 2021)
The aim of this study is to assess the efficiency of psyllium husk ethanolic extract (PHEE) on Triton X-100 induced hyperlipidemic rats by studying the changes in hepatic and pancreatic function and histopathology. Forty male albino rats (bodyweight 175–188 g) were grouped randomly into four sets with ten rats. The experimental groups included: (1) control group (CON); (2) Triton X-100 induced hyperlipidemic group—rats were intraperitoneally injected with a single dose of Triton X-100 (100 mg/kg body weight) on the 21st day of Trial onset; (3) PHEE group—PHEE was orally administered (100 mg/kg body weight dissolved in 1 mL of distilled water) by gastric tube from the first day of the experiment until the fortieth day, once daily, (PHEE); (4) PHEE +Triton group, which received PHEE orally with the induction of hyperlipidemia. Treating hyperlipidemic rats with PHEE showed a decrease in the total serum lipids, triglyceride (TG), total cholesterol (TC), atherogenic index (AI), and malondialdehyde (MDA) with an increase in superoxide dismutase (SOD) and catalase (CAT) activities. PHEE administration alleviated the negative impact of Triton on the serum levels of glucose, insulin, glycated hemoglobin (HbA1c), homeostatic model assessment for insulin resistance (HOMA IR index), leptin hormone, Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST), Gamma-Glutamyl Transferase (GGT) and proteinogram. The Triton-induced hyperlipidemic rats showed extensive histopathological changes in the liver and pancreas, which were alleviated with PHEE administration. It could be concluded that PHEE has potent effects against hyperlipidemia, hyperglycemia, and oxidative stress due to its biologically active constituents detected by GC-MS analysis. This study’s findings may help develop a novel trial against the effects of hyperlipidemia in the future.